2020
DOI: 10.1108/imds-10-2019-0573
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and consequences of the perceived positive eWOM review credibility

Abstract: PurposeThis study explores the effects of interpersonal determinants (tie strength and homophily) and informational determinants (source trustworthiness and customer endorsement) on perceived positive electronic word-of-mouth (eWOM) review credibility (PPERC), which subsequently affects attitude toward the product (ATP), attitude toward the Fan Page (ATFP), and eWOM review adoption (ERA) based on the cognition-affection-behavior (CAB) model.Design/methodology/approachThe research sample consists of 402 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 134 publications
4
41
0
Order By: Relevance
“…This dominance is most likely attributed to the study's context, which is UGC on beauty products. Near similar gender composition was also observed in other eWOM studies involving beauty and fashion products (Cheung et al , 2014; Chih et al , 2020). The imbalanced gender composition is not considered a methodological issue since neither male nor female viewers showed significantly different trustworthiness ratings based on whether they were watching a broadcaster of the same or opposite sex (Todd and Melancon, 2018).…”
Section: Data Analysis and Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This dominance is most likely attributed to the study's context, which is UGC on beauty products. Near similar gender composition was also observed in other eWOM studies involving beauty and fashion products (Cheung et al , 2014; Chih et al , 2020). The imbalanced gender composition is not considered a methodological issue since neither male nor female viewers showed significantly different trustworthiness ratings based on whether they were watching a broadcaster of the same or opposite sex (Todd and Melancon, 2018).…”
Section: Data Analysis and Resultssupporting
confidence: 85%
“…This research population was respondents who have viewed and consumed voluntary UGC on beauty and skincare products through YouTube videos. This method follows several eWOM studies that focused on beauty products (Cheung et al , 2014; Chih et al , 2020; García-de-Frutos and Estrella-Ramón, 2021), considering its broad online audience appeal. Besides, as many as 80% of consumers are inclined to purchase health and beauty products online (Accenture Research, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…They found this influence to be intensified when the personal identifying information of the reviewer was available. Similarly, Chih, Hsu and Ortiz found that interpersonal determinants such as tie strength and homophily, and information determinants such as source trustworthiness and customer endorsements had a significant positive effect on the perceived eWOM credibility [23]. Kim, Kandampully and Bilgihan also found a similar relationship between homophily and tie strength with source credibility which in turn influenced their attitude towards eWOM [24].…”
Section: Introductionmentioning
confidence: 80%
“…Prior studies also find that online review credibility can improve consumers' attitudes toward the message source (Chih et al, 2013(Chih et al, , 2020Filieri et al, 2020). We, therefore, hypothesize that if a rumor is perceived as more credible, the receiver will have a greater intention to retransmit the rumor in order to seek status because a credible rumor can help build a reputation.…”
Section: Attractivenessmentioning
confidence: 91%